(untitled) (Acta Scientiarum. Biological Sciences, 2016)
Bromeliads are an important group for the maintenance of the Atlantic Forest, with many threatened species due to exacerbated extraction and destruction of their natural habitats. Considering the need of developing protocols for the conservation of these species, the aim of this work was to evaluate the effect of different growth regulators in the in vitro induction of shoots of Billbergia euphemiae. Leaf explants were excised from seedlings derived from in vitro germination and grown on MS medium supplemented with NAA (0, 1 or 2 Î¼M) and BA (0, 2, 4 or 6 Î¼M) combinations. The evaluation of the number of shoots per explant, shoot length, number of leaves per shoot and longest leaf length average was carried out after 30 and 60 days of culture. The best in vitro responses were observed in the presence of 1 Î¼M NAA after 60 days of culture, which induced the best production of shoots per explant (16.39), as well as the highest rates of shoot length (1.08 cm), number of leaves per shoot (5.00) and the longest leaf length (0.56 cm). This work determined the best conditions for shoot production from leaf explants of B. euphemiae, being the first report on micropropagation of this species.